Liberalizing Telecommunications and the Role of the World Trade Organization - Primo Braga, Carlos A. (World Bank, Washington, DC, 2012)
In February 1997, sixty-nine governments of high-income and developing countries agreed to liberalize their basic telecommunications services under an agreement negotiated through the World Trade Organization. Most participants in the agreement have subscribed to procompetitive regulatory principles, including independent regulators, competitive safeguards, measures to ensure interconnection, universal service obligations, and transparent and nondiscriminatory practices in licensing. The markets affected by the arrangement represent more than 90 percent of the world market for telecommunications. The author reviews the evolution of the agreement and argues that the critical issues now are ensuring the quality of implementation and setting up a procompetitive regulatory environment.